The Conductivity Change in the Course of Ion Exchange Chromatography: Effects on the Biological Activity and Isoforms of Human Recombinant Erythropoietin - Mardani, Rajab; Daneshmand, Fatemeh; Haghirolsadat, Fatemeh; Kalantar, Mehdi (Archives of Advances in Biosciences, 2019)
r Introduction: Recombinant human erythropoietin (rhEPO) has been produced in different conditions and cell lines. Identification, isolation, and purification of this protein from various sources have pivotal role in clinical applications. Hence, Clinical trials should be carried out for the identification of purity and aggregation of biological EPO. Moreover, the purification of EPO cooperates with various recommended processes has been manifested, but the strategies schemes (i.e., liquid chromatography (HPLC) and ion exchange chromatography (IEX) are often used in combination. In the current study, the quality of purification, biological modifications and the stability of rhEPO using various chromatography methods including HPLC and IEX have been assessed. Materials and Methods: rhEPO was expressed in the Chinese hamster ovary (CHO) cells and purified by the general requirements for the quality control of biological products. For the assessment of the influence of IEX in the purity pattern of rhEPO, HPLC and biological analysis were performed for 3 samples. Results: Our results revealed that the combination of 4 strategies represent confident methods for evaluating the quality of this biological medicinal product; moreover, purity and biochemical applications will yield to a relatively pure protein preparation. The activity of EPO was presented by monomeric isoform and high acid sialic purification in final product. Moreover, the determination of the biochemical reactions rate and their relationship tests were obtained by change in electrical conductivity with pH being 31.5 and 5, respectively. Conclusion: Taken together, our results indicated that different purification process based on our results can increase the accuracy of rhEPO purification.